Perancangan Game Visual Novel Menggunakan Ren'Py Berbasis Android - Muslihuddin, Muslihuddin; Rosmawanti, Nidia (STMIK Banjarbaru, 2024)
Stories in visual novels can vary widely, including romance, mystery, science fiction, fantasy, and horror. Visual Novel Games in the horror genre, more precisely included in the Visual Novel horror subgenre, are very popular because they provide a special sensation for those who like horror, where players are often faced with important decisions that influence the course of the story, thus providing many different possible endings. by providing gripping events. In the research carried out, the real story in West Kalimantan was based on the urban legend